Media and extremism from the anti-extremism activist perspective in Southeast Asia - Ahmad Munawar Ismail (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2022)
It is an undeniable fact that the dangers of this extremism threat had created propaganda that led to a misunderstanding about Islam. This misconception affects religious harmony in society, and even some of them are trapped in interpreting the issue. The action is hostile and tarnishes the image of Islam. At the same time, the fact of the involvement of some Muslims in this issue is still uncertain and mostly driven by misunderstandings of Islamic teachings. This article discusses the views of anti-extremism activists in Southeast Asia on the role of the media in issues related to religious extremism. The debate is part of the findings of a study on the collective approach to addressing the ideology of extremism in Malaysia. The results of a semi-structured interview with a total of 10 experts were referred for the discussion. The experts were from various agencies including academics, counsellors of the Malaysian Prison Department, the Head of State Islamic Religious Council Research Division, Department of Islamic Development Malaysia (JAKIM), officers from the Malaysian Armed Forces (ATM) and research fellows of extremism from other countries in Southeast Asia such as Chairman of al-Salam Institute in Thailand, Chairman of Religious Rehabilitation Group (RRG) in Singapore, research fellow of Counter Terrorism Division, S. Rajaratnam from the School of International Studies, Nanyang Technological University (NTU) of Singapore and others. The findings showed that all the interviewed participants agreed that extremism is outrageous acts disclosed by the followers in all aspects including religion, politics and ideology. Besides that, the media agreed that they play a significant role in portraying the news reporting of extremism with the religion. They also agreed that the movement of extremist activities differs from one country to another. Thus, the approach to dealing with it should also be different but need to go through a process of consultation.